Maqasid Al-Shariah approach - Md Nor, Nurhidayah; Zakariyah, Luqman; Mahmud, Mek Wok (IIUM Press, International Islamic University Malaysia, 2017)
The dispute in the management of Tabung Masjid (TM) has been widely discussed in previous studies. However, the awareness in overcoming these issues are not given adequate attention. As the concept of Maqāṣid al-Sharī‘ah (objectives of Sharīah) is to serve the interest of all human beings and to save them from harm as, the use of this concept would help mosques to practise the effective management of TM. Therefore, this study attempts to scrutinise the management of TM in Selangor according to the Maqāṣid al-Sharī‘ah and thereby, examine the challenges faced by TM in Selangor that could prevent TM to be managed according to the Maqāṣid al-Sharī‘ah. For this purpose, the authors conducted a survey on the management of TM in Selangor and analysed the relationship between TM in Selangor and the Maqāṣid al-Sharī‘ah in Islamic Jurisprudence. This study also presents the ways of managing TM in Selangor from the point of view of the Maqāṣid al-Sharī‘ah and explicates how this approach could offer better solutions for various TM issues and challenges. The result of this study can help improve the management of TM in Selangor as well as reduce the socio-economic problems in the society.